Unveiling the Phenomenon of Strava Jokis: The Ethics of Digital Lifestyle in the Spotlight of Islamic Economics and Maqashid Shariah - A. Rio Makkulau Wahyu; Wirani Aisiyah Anwar; Heri Irawan; Srianti Permata; Hasmia Wahyunisa (Universitas Islam Negeri Alauddin Makassar, 2024)
This study examines the phenomenon of Strava jokis within the context of digital lifestyle ethics and Islamic economics. Strava jokis refer to the practice where someone pays another person to manipulate their sports activity data on the Strava app in order to gain social recognition on digital media. The research employs a qualitative method with a literature review approach to analyze the Strava jokis phenomenon through relevant literature on digital ethics and Islamic economics. The findings indicate that this phenomenon reflects the strong impact of social media on individual behavior, where people often pursue image and social validation while neglecting values such as honesty and authenticity. Social pressure drives manipulative behavior that damages personal integrity and mental health due to the practice of manipulation. The Strava jokis phenomenon contradicts the principles of Maqashid Shariah, and from an Islamic economics perspective, the service of Strava jokis conflicts with fundamental principles such as honesty, justice, and transparency, as it involves deception that harms society and disrupts the social order. Therefore, a stronger ethical approach to the use of technology and social media is needed, emphasizing moral values and Islamic principles to create a more responsible digital lifestyle.